The Secrets of Alternative Autophagy - Kaja Urbańska (MDPI AG, 2021)
For many years, it was thought that ATG5 and ATG7 played a pivotal role in autophagy, and that the knockdown of one of these genes would result in its inhibition. However, cells with ATG5 or ATG7 depletion still generate autophagic vacuoles with mainly trans-Golgi-originated isolation membranes and do not die. This indicates that autophagy can occur via ATG5/ATG7-independent alternative autophagy. Its molecular mechanism differs from that of the canonical pathway, including inter alia the phosphorylation of ULK1, and lack of LC3 modifications. As the alternative autophagy pathway has only recently been described, little is known of its precise role; however, a considerable body of evidence suggests that alternative autophagy participates in mitochondrion removal. This review summarizes the latest progress made in research on alternative autophagy and describes its possible molecular mechanism, roles and methods of detection, and possible modulators. There is a need for further research focused on types of autophagy, as this can elucidate the functioning of various cell types and the pathogenesis of human and animal diseases.